Model of Behaviour Intention Factors on Social Media Use for Collaborative Learning - Nur Shamsiah, Abdul Rahman; Mohd Shahizan, Othman; Anis Farihan, Mat Raffei; Eh Phon, Danakorn Nincarean; Adzhar, Kamaludin (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
Despite technologies of social media gaining acceptance in universities all around the world, the study on factors of students’ behavioural intention to use social media for collaborative learning have not been fully explored in Malaysia and useful insights are still needed to resolve this problem. Thus, this project examined influential factors on students’ behavioural intention to use social media for active collaborative learning that affects teaching and learning. This study developed a theoretical model based on Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use Technology (UTAUT), and constructivism theory. The findings of the study revealed that perceived ease of use, perceived usefulness, perceived enjoyment, performance expectancy, social influence, and facilitating conditions are positively related to students’ behavioural intention toward the use of social media for collaborative learning purpose. Based on the study, the use of social media is significant and positive for collaborative learning and teaching in Malaysian Higher Education institutions.